The evolution from strict liability to fault in the law of torts - Gray, Anthony (Law teacher) (Oxford, UK ; Hart Publishing, an imprint of Bloomsbury Publishing, 2020)
"Gradually, the law of tort has shifted away from a strict-liability approach to one where fault predominates. This book charts important case law documenting this shift. It seeks to understand how and why it occurred. Given that the Rylands v Fletcher decision is typically seen as a prime exemplar of strict liability, it focusses particularly on that case, as part of the historical development of tort law. It considers the intellectual arguments made in favour of strict liability, and for fault-based liability. Having done so, it then focusses on particular areas of the law of tort, including nuisance, defamation and trespass. It is somewhat anomalous that though most would view these as examples of torts of strict liability, fault considerations have become prominent in their application. This presents an uneasy compromise, where torts that are notionally strict in nature are infused with fault considerations, often through exceptions or defences. This book advocates for further development in the law of tort to better reflect a primarily fault-based approach to liability, at least in the common law. This would make the law of tort more coherent"--
Strict liability and the common law -- Strict liability and particular torts in legal history -- Rylands v Fletcher in the United Kingdom -- Comparative approach to Rylands v Fletcher liability -- Summary of the theoretical debate : strict liability and fault-based liability -- Critical reflections on the justifications for strict liability -- The tort of nuisance and fault -- Strict liability in the law of defamation -- Trespass and fault.
Includes bibliographical references and index.
Also published in print.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Mode of access: World Wide Web.
Keywords: Strict liability -- Great Britain; Torts -- Great Britain; Torts / Delicts; Electronic books